Corneal curvature changes in soft and rigid gas permeable contact lens wearers after two years of lens wear - (:unkn) unknown (My University, 1996)
PURPOSE: To determine the changes in corneal curvature among soft and rigid gas permeable (RGP) contact lens wearers, we compared horizontal, vertical, and total astigmatism values in 80 subjects before and after 2 years of contact lens wear. METHODS AND RESULTS: The soft contact lens wearer group was composed of 40 subjects. The changes in corneal curvature that occurred in this group over the 2-year study period were not statistically significant. The RGP contact lens group also comprised 40 subjects. This group, however, did show significant steepening in vertical axis, but changes in corneal astigmatism values were not statistically significant. CONCLUSIONS: The high oxygen transmissibility and relative flexibility of RGP contact lenses compared to polymethylmethacrylate contact lenses may be the factors responsible for the limited corneal curvature changes that occurred during our 2-year study.
Keywords: Adult; Female; Humans; Middle Aged; Treatment Outcome; Adolescent; Male; Follow-Up Studies; Cornea; Contact Lenses; Astigmatism; Contact Lenses, Hydrophilic